Pancoh Bercerita: Storynomics dalam Pengemasan Promosi Paket Wisata Seni dan Budaya - Sari, Yulita Kusuma; Sushartami, Wiwik; Aji, Khusnul Bayu (Gadjah Mada Journal of Tourism Studies, 2022)
The COVID-19 epidemic has impeded tourism activities worldwide. Pancoh Ecotourism Village is an instance of a tourist destination that was compelled to cease its operations amid the pandemic. Nevertheless, that does not imply that nothing can be accomplished.   Amidst the pandemic, it is imperative to create tourism offerings that are more inventive in order to adapt to the new normal period. The Pancoh Ecotourism Village offers an innovative tourism package that combines art and culture based on the concept of storynomics. This study employs the Participatory Action Research (PAR) method to engage village communities as active participants, rather than just sources of information. The aim is to involve them in the process of gathering, organizing, and presenting narratives about the local arts and culture that define the Ecotourism Villages of Pancoh.   This study discovered that the PAR technique is beneficial for students who are examining the extent of community involvement in developing a work plan, namely in this case, the creation of tour packages based on storynomics. However, PAR encounters challenges such as extended research duration, varying levels of informant motivation, and the researcher's requirement for considerable adaptability in terms of time and ability to engage with informants.